Third SARS-CoV-2 vaccination and breakthrough infections enhance humoral and cellular immunity against variants of concern - Ruhl, Louisa; Kühne, Jenny F.; Beushausen, Kerstin; Keil, Jana; Christoph, Stella; Sauer, Jasper; Falk, Christine S. (Frontiers in Immunology, 2023)
SARS-CoV-2 vaccination is the leading strategy to prevent severe courses after SARS-CoV-2 infection. In our study, we analyzed humoral and cellular immune responses in detail to three consecutive homologous or heterologous SARS-CoV-2 vaccinations and breakthrough infections. All individuals (n=20) responded to vaccination with increasing S1-/RBD-/S2-specific IgG levels, whereas specific plasma IgA displayed individual variability. The third dose increased antibody inhibitory capacity (AIC) against immune-escape variants Beta and Omicron independently of age. The mRNA-primed vaccination induced IgG and IgA immunity more efficiently, whereas vector-primed individuals displayed higher levels of memory T and B cells. Vaccinees showed SARS-CoV-2-specific T cell responses, which were further improved and specified after Omicron breakthrough infections in parallel to the appearance of new variant-specific antibodies. In conclusion, the third vaccination was essential to increase IgG levels, mandatory to boost AIC against immune-escape variants, and induced SARS-CoV-2-specific T cells. Breakthrough infection with Omicron generates additional spike specificities covering all known variants.